Empathy Assessment Among Medical Students Towards Patients - A Cross-Sectional Study - Subha Lakshmi; Tamilchelvan, Vignesh; Sevvanthi K; Arunachalam D (National Journal of Community Medicine, 2024)
Background: Empathy is the student’s understanding of the patient’s experience and ability to convey the feeling. Empathy is teachable and measurable, and proper teaching to students about ethics, humanity, and professionalism can improve patient care.1 This study tries to determine the empathy levels among medical college students towards patients and the variation in empathy levels among medical college students towards patients each year. Methodology: The sample size was 400, undergraduate students from 1st year to compulsory rotating medical internship were selected. Results: There was a significant association between empathy levels and year of education and as the year of study increases the empathy level decreases and this is statistically significant. Conclusion: The empathy level of medical students is at good levels. Still, the empathy level is declining as the year of studies increases because of the stress in studies and increased patient load.